Innovative non-destructive technologies for quality monitoring of pineapples: recent advances and applications - Mohd Ali, Maimunah; Hashim, Norhashila; Bejo, Siti Khairunniza; Jahari, Mahirah; Shahabudin, Nurul Aqilah (Elsevier, 2023)
Background: Pineapples are important tropical fruits which serve as a vital source of minerals and have excellent nutritional composition. The quality evaluation of pineapple is an important factor in consumer preference, postharvest handling, and the commercial value of the fruit. Scope and approach: In this review, the external and internal quality attributes of pineapples are presented. This review also discusses the application of chemometrics and data mining which have been used to evaluate the quality attributes of pineapples. In this sense, non-destructive technologies have gained interest to ensure fruit quality evaluation since it offers a safer and more reliable way that is cost-effective without damaging the fruit. Key findings and conclusions: Special attention is focused on the emerging non-destructive technologies along with a comprehensive review of the applications of these technologies. Spectroscopy-based, computer vision, imagingbased, acoustic, ultrasound, and instrument-based sensing technologies are innovative non-destructive technologies that can be used as promising alternatives to the conventional method to effectively monitor the quality of pineapples. The challenges and future trends in the quality evaluation of pineapples using non-destructive technologies have been addressed.